IMPLEMENTATION OF HEALTH PROMOTION MEDIA POLICY AT HEALTH FACILITIES: A CASE STUDY AT RAPPANG PUBLIC HEALTH CENTER, SIDENRENG RAPPANG REGENCY - Nurfadilah Ruslan; Devy Febrianti; Zulkarnain Sulaiman; Sunandar Said (JTH: Journal of Technology and Health, 2026)
Health promotion plays an important role in improving public health through the delivery of planned and sustainable health information. As a primary healthcare facility, community health centers (Puskesmas) have a strategic role in implementing health promotion media policies. This study aimed to analyze the implementation of health promotion media policies at Rappang Public Health Center, Sidenreng Rappang Regency, based on Warwick’s policy implementation theory, which includes organizational capability, support, information, and resource allocation. This study employed a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews, observation, and documentation, and analyzed using thematic analysis with the assistance of NVivo 12 Plus software. The results showed that the implementation of health promotion media policies has generally been carried out well. Organizational capability was reflected in program planning and implementation based on activity targets, although specific standard operating procedures were not yet available. Support from leadership, adequate facilities, and cross-sector collaboration contributed to program implementation. Health information was disseminated through both printed and digital media, while resource allocation remained constrained by limited personnel and multiple responsibilities among health promotion officers. The study concludes that the implementation of health promotion media policies at Rappang Public Health Center has been effective; however, improvements in standard operating procedures and human resource capacity are needed to enhance program effectiveness.